Crop residue trade-offs project: Content lessons and gaps - International Livestock Research Institute (International Livestock Research Institute, 2010)
From 9-10 December 2010, Researchers in a project carrying out four regional cases studies of 'crop residue trade-offs in crop–livestock systems' met in Addis Ababa to review progress and plans. We recorded the reporting back sessions that discussed lessons and gaps related to the content focus of the project, the process followed so far, and the tools used. Here, Alan Duncan, reports on the content discussions. Some 'gaps': Are the survey tools capturing sufficiently the higher-level policy and institutional environment? Are we capturing more open questions about how farmers make decisions? On the lessons: we need to better integrate the social with the technical; and we need to keep our eyes on the global drivers, as well as the regional ones. The meeting was organized by the CGIAR Systemwide Livestock Programme (SLP).